A note on some Eocene benthic foraminifers of West and Central Iran, with remarks on palaeontology and biostratigraphy: Reply to Hadi and Schlagintweit comment (2024)☆ - Babazadeh Seyed Ahmad; Cluzel Dominique (BSGF - Earth Sciences Bulletin)
This article is a reply to the comment by Hadi and Schlagintweit (2024, Acta Palaeontologica Romaniae 2: 17–2) on the article by Babazadeh and Cluzel (2023, Bulletin de la Société Géologique de France 194: 1–24) about the internal structure and stratigraphic range of some benthic foraminifers from the Eocene carbonate deposits in the Shahr-e Kord and Mahallat regions of Iran. The comment focuses on the diagnosis of a limited number of species, and the introduction of new species of Eocene agglutinated foraminifers from the Mahallat region. In this reply, the disputed data are briefly reviewed and discussed in more detail. The interpretation of benthic foraminifers is based on their morphological variability and comparisons. Here the authors use re-illustrations of the types of nummulitids (Nummulites), orbitolinids (Coskinolina, Daviesiconus, Coleiconus and Barattolites), and other comparative material to confirm their determinations. Therefore, the hyaline foraminifers constitute the main subject of investigation, whereas the alveolinids are of secondary importance.